Mandibular Resection in Pediatric Patient with Extensive Fibromyxoma: A Case Report - Nicolas Solano; Bairon Castro; Ligia Perez; Ariamay Castrillo (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Myxomas of the jaws are considered to arise from odontogenic ectomesenchyme. This pathology is most commonly found in young adults, but it may appear across a wide age group with an average age from 25 to 30 years with no sex predilection. We present a case of a 2-year-old male pediatric patient with the increased facial volume on the right side and six months of evolution without presenting symptoms, with the diagnosis of fibromyxoma, where a surgical resection through hemimandibulectomy with disarticulation and immediate costal graft reconstruction was performed. It was an uncommon case due to its extension and prolonged evolution time, which represented a challenge in our particular environment. Surgical resection may be required because myxomas are not encapsulated and, because of their consistency, they may infiltrate the surrounding bone. Long-term clinical and radiological follow-ups should be undertaken due to the risk of recurrence.